Clinical anatomy for medical students - Snell, Richard S. (Lippincott Williams & Wilkins, Philadelphia, 2000)
"The new edition of Clinical Anatomy for Medical Students is created with today's curriculum and medical practice in mind." "Taking into account the vast expansion of technology in recent years, the new Sixth Edition delivers high-yield content in a concise format with everything you need for your future in practice - without extraneous detail." "Like its predecessors, the Sixth Edition features a user-friendly organization by body region, from surface to deep structure. That way, the presentation is in sync with your curriculum, and also makes it easier to find material on specific structures." "Plus, the book is generously illustrated, with clear depictions augmented with extensive use of color. You'll find artwork summarizing the nerve and blood supplies of regions, as well as overviews of the distribution of cranial nerves - an advantage for study and review."--Jacket.
Ch. 1. Introduction -- Ch. 2. The Thorax: Part I. The Thoracic Wall -- Ch. 3. The Thorax: Part II. The Thoracic Cavity -- Ch. 4. The Abdomen: Part I. The Abdominal Wall -- Ch. 5. The Abdomen: Part II. The Abdominal Cavity -- Ch. 6. The Pelvis: Part I. The Pelvic Walls -- Ch. 7. The Pelvis: Part II. The Pelvic Cavity -- Ch. 8. The Perineum -- Ch. 9. The Upper Limb -- Ch. 10. The Lower Limb -- Ch. 11. The Head and Neck -- Ch. 12. The Back.
Includes index.
Keywords: HUMAN ANATOMY; CLINICAL ANATOMY